Northern Mediterranean climate since the Middle Pleistocene: a 637 ka stable isotope record from Lake Ohrid (Albania/Macedonia) - Lacey, Jack H.; Leng, Melanie J.; Francke, Alexander; Sloane, Hilary J.; Milodowski, Antoni; Vogel, Hendrik; Baumgarten, Henrike; Zanchetta, Giovanni; Wagner, Bernd (European Geosciences Union, 2016)
Lake Ohrid (Macedonia/Albania) is an ancient lake with unique biodiversity and a site of global significance for investigating the influence of climate, geological, and tectonic events on the generation of endemic populations. Here, we present oxygen (δ18O) and carbon (δ13C) isotope data from carbonate over the upper 243 m of a composite core profile recovered as part of the Scientific Collaboration on Past Speciation Conditions in Lake Ohrid (SCOPSCO) project. The investigated sediment succession covers the past ca. 637 ka. Previous studies on short cores from the lake (up to 15 m, < 140 ka) have indicated the total inorganic carbon (TIC) content of sediments to be highly sensitive to climate change over the last glacial–interglacial cycle. Sediments corresponding to warmer periods contain abundant endogenic calcite; however, an overall low TIC content in glacial sediments is punctuated by discrete bands of early diagenetic authigenic siderite. Isotope measurements on endogenic calcite (δ18Oc and δ13Cc) reveal variations both between and within interglacials that suggest the lake has been subject to palaeoenvironmental change on orbital and millennial timescales. We also measured isotope ratios from authigenic siderite (δ18Os and δ13Cs) and, with the oxygen isotope composition of calcite and siderite, reconstruct δ18O of lake water (δ18Olw) over the last 637 ka. Interglacials have higher δ18Olw values when compared to glacial periods most likely due to changes in evaporation, summer temperature, the proportion of winter precipitation (snowfall), and inflow from adjacent Lake Prespa. The isotope stratigraphy suggests Lake Ohrid experienced a period of general stability from marine isotope stage (MIS) 15 to MIS 13, highlighting MIS 14 as a particularly warm glacial. Climate conditions became progressively wetter during MIS 11 and MIS 9. Interglacial periods after MIS 9 are characterised by increasingly evaporated and drier conditions through MIS 7, MIS 5, and the Holocene. Our results provide new evidence for long-term climate change in the northern Mediterranean region, which will form the basis to better understand the influence of major environmental events on biological evolution within Lake Ohrid.